Przyczynek do badań nad ramą wydawniczą utworów dramatycznych Wincentego Ignacego Marewicza - Petlak, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper aims to promote a neglected, and consequently little‑known, writer of the period of the Polish Enlightenment – Wincenty Ignacy Marewicz (1775–1822), the author of, among others, poems, writings in verse and prose, a collection of sayings, as well as comedies, dramas and an opera. The publication discusses some of the elements of the publishing framework (including dedications, prefaces, epigraphs, and lists of works already published) which the writer used in his dramatic works and which include important information about him, his work and life. The paper is a kind of reconnaissance to pave the way for further research on the above‑mentioned subject.